2006
DOI: 10.1123/jpah.3.s1.s77
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Walking for Transportation or Recreation Purposes

Abstract: Physical environment contributed significantly to explain the probability of walking. However, different attributes of environment were related to transportation versus recreation walking, suggesting the need for multiple and targeted interventions to effectively support walking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
194
5
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(233 citation statements)
references
References 31 publications
17
194
5
5
Order By: Relevance
“…Also, specific land use can instigate leisure travel [8], as well as generally influence it [14]. These findings result in H3.…”
supporting
confidence: 50%
See 2 more Smart Citations
“…Also, specific land use can instigate leisure travel [8], as well as generally influence it [14]. These findings result in H3.…”
supporting
confidence: 50%
“…Vegetation is preferred to dwellings for leisure travel as predicted in H4 and found previously [12]; however, land use ranks only equal third rather than first as expected [14]. This may be a reflection of the images used for this attribute, and discussions held after the experiment indicated that participants had considered other factors such as weather when selecting a route.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Transport planning research has focused on mode choice, not on access to different modes, and there is a less well-established literature on how far pedestrians walk and the factors that influence their route choice (Agrawal et al 2008). There is increasing interest in the relationship between walking and health from public-health researchers, with studies on walking as a mode by Corpuz et al (2005), Lee andMoudon (2006), andMerom et al (2010), and on walk time to meet physical activity requirements (Besser and Dannenberg 2005). For walk as a mode in itself, there is some evidence that recreational walking trips, which include trips for exercise and fitness, are longer than for other purposes (Corpuz et al 2005;Iacono et al 2008), although Iacono et al (2008) noted that distance decay functions are similar across trip purposes.…”
Section: Influences On Walking Distancementioning
confidence: 99%
“…[10][11][12] Generally, it is known to be associated with adults' transport-related physical activity, as higher residential density means more destinations such as shops, services, and public transport stops nearby. 13 With regard to the association between adolescents' recreational activity and residential density, mixed findings have been reported from a small number of studies. One such study conducted in the USA showed that an index of neighborhood walkability, which includes residential density, to be positively associated with moderate-to-vigorous physical activity in adolescents aged 14-17 years.…”
Section: Introductionmentioning
confidence: 99%